DOES INDUSTRIAL WORK PRACTICE EXPERIENCE AND VOCATIONAL COMPETENCE STRENGTHEN WORK READINESS THROUGH EMPLOYABILITY SKILLS? - Yulianti, Devi; Wolor, Christian Wiradendi; Adha, Maulana Amirul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This study was conducted to determine the effect of industrial work practice experience and vocational competence on job readiness through employability skills at State Vocational High School 3 Depok. The research method used is quantitative research method with a descriptive approach. The population used in this study were students of State Vocational High School 3 Depok in all expertise programs, namely Construction and Property Business, Computer and Network Engineering, Online Business and Marketing, Accounting and Institutional Finance, Islamic Banking and Office Management Automation consisting of 450 students with a sample of 212 students. This research model uses a path analysis model and the data analysis technique used is SEM (Structural Equation Modeling) using the SmartPLS version 3 application. This shows that industrial work practice experience and vocational competence have a positive and significant direct effect on work readiness, and also have indirect effect through employability skills.